The indication and curative effect of hysteroscopic and laparoscopic myomectomy for type II submucous myomas. Issue 1 (December 2016) - Wang, Haibo; Zhao, Jinrong; Li, Xiujuan; Li, Ping; Lu, Caihong; Tian, Shujuan; Wang, Zhong-hua
Abstract Background The aim of this study was to assess curative effect of hysteroscopic and laparoscopic myomectomy for type II submucous myomas between 3 and 5 cm in diameter and explore the optimal surgical indications. Methods A retrospective analysis was performed of those who underwent hysteroscopic or laparoscopic myomectomy from January 2008 to January 2013. The patients were divided into three subgroups according to the myomas diameter (namely, 30 mm ≤ myomas diameter <40 mm; 40 mm ≤ myomas diameter <50 mm; and myomas diameter ≥ 50 mm). Clinical data such as operation time, amount of bleeding, postoperative anal exsufflation time, hospital stay, and complications were collected. Results There was no significant difference regarding operation time and amount of bleeding in two groups. We found significant difference in hysteroscopic group (within-subgroup) difference regarding operation time and amount of bleeding, whereas no significant difference in the laparoscopic group, while significant differences between-subgroup differences regarding operation time. Complete removal of myoma was seen in all patients. Conclusions Both techniques are feasible for type II submucous myomas. Laparoscopic operation has higher advantages in type II submucous myomas of greater than 4 cm in diameter whereas hysteroscopic operation has higher advantages in type II submucous myomas of lower than 4 cm in diameter.